Intellectual property and innovation process (sustainable development goal 17) - Antošová, Gabriela; Cifuentes Valenzuela, Jorge (2021)
This paper represents a conceptual discussion focused on the basic vision of science and technology, which is the main purpose and reference framework of the produced United Nations’ documents and of the presented Sustainable Development Goals (SDGs) of the 2030 Agenda. The most important evident intention and the objective of these documents is the technology transfer, which carries a risk of not recognizing other technological options, such as echo-technology, and of course, also the limited role representing science and innovation in the achievement of these Sustainable Development Goals.